Report template on integrating impact into an existing monitoring and evaluation system (Methods Lab, 2015)
Many development programme staff will commission an impact evaluation towards the end of a project or programme, only to find that the monit oring system did not provide adequate data about implementation, conte xt, baselines or interim results. This tool provides a template outlin e for a report making recommendations on how to integrate a focus on i mpact into a programme’s existing monitoring and evaluation system, as the programme moves into a new phase. This template was developed by Anne Buffardi and Tiina Pasanen for use in Methods Lab projects.